The chef - Patterson, James, 1947-; DiLallo, Max (New York : Little, Brown and Company, 2019)
Accused of committing murder in the line of duty, detective Caleb Rooney of the New Orleans PD uses the contacts from his moonlighting job as a celebrity food-truck chef to counter a terrorist plot.
Keywords: Detective and mystery stories; Cooks -- Fiction; Detectives -- Fiction; Cooks -- Fiction; New Orleans (La.) -- Fiction; New Orleans (La.) -- Fiction; Mystery fiction; Suspense fiction; Suspense fiction; Mystery fiction; Detective fiction; Mystery fiction